An emergency urology skills course for the multidisciplinary team. (May 2023) - Gallagher, Jessica; Crockett, Matthew; McMeekin, Faith
Urological presentations account for approximately 1.7% of emergency hospital admissions, 7.8–20% of the acute surgical take and 5–10% of visits to general practice. Training in this area is often unsatisfactory, with a third of final year medical students not feeling confident in managing urological emergencies and 6% receiving no exposure at all. Urology is a multidisciplinary speciality, and many emergency urological presentations require urgent treatment with specialised equipment or skills. A quality improvement project was set up at Gloucestershire Hospitals NHS Foundation Trust with the aim of improving experience and confidence among junior doctors and allied health-care professionals with common urological practical skills using a simulation-based course. There was an emphasis on multidisciplinary team working to mirror the clinical environment. Pre-course questionnaires showed that most participants lacked confidence with common urology practical skills, such as haematuria management (80–85%), nephrostomy management (93–95%) and suprapubic catheters (93–100%). After attending the course, confidence improved in all skills, and participant satisfaction was high, with 100% finding the course relevant to clinical practice. The course was run at low cost, free to participants and without the need for long periods of study leave, making it accessible to all. We suggest the model of this course could be easily transferred to other hospital trusts and applied to other surgical specialities for similar simulated training. Level of evidence: Level 5.